Chinese Water Systems Volume 1: Liaohe and Songhuajiang River Basins (Terrestrial Environmental Sciences,, 2018)
This book describes the huge efforts by the Chinese Government concerning the restoration and future sustainable management of Chinese water systems. It presents the results of a Sino-European joint project concerning the Songhuajiang-Liaohe River-Basin (SLRB) in Northeast China conducted by the Chinese Research Academy of Environmental Sciences (CRAES), the Helmholtz Centre for Environmental Research - UFZ, Germany, and the Natural Environment Research Council as represented by the Centre for Ecology and Hydrology (CEH), UK. The book explains in great detail the development of risk assessment and corresponding management methods for (i) controlling water pollution, (ii) assessing river health and ecological restoration options, (iii) characterizing persistent organic pollutants (POPs), and (iv) protecting fragile groundwater resources. It also describes the implemented demonstration sites of SLRB during the project course as well as lessons learnt on efficient project management and the dissemination of knowledge and technologies.